EFFECT OF HANTU PLANT GROWTH REGULATOR (PGR) DOSE AND TAWON NPK FERTILIZER APPLICATION ON GROWTH AND YIELD OF PAKCHOY (Brassica rapa L.) - Yendra Zuvijal; Sri Susanti Ningsih; Heru Gunawan (Bernas : Jurnal Penelitian Pertanian, 2018)
The research was conducted at experimental garden of University of Asahan, with flat topography and high place ± 15 m asl. The research was conducted from March to April 2018. This research used Randomized Block Design using Factorial Treatment Plan which consist of 2 factors: PGR Hantu dose (Z) with 3 treatments: Z0: 0 cc / l water, Z1: 2 cc / l water, Z2: 4 cc / l water. Dosage of NPK Tawon (N) with 4 treatments, ie: N0: 0 kg / ha 0 g / plot, N1: 187.5 kg / ha18.75 g / plot, N2: 375 kg / ha 37.50 g / plot, N3: 562.5 kg / ha 56.25 g / plot. The observed variables are: Plant height (cm), Number of Leaves (Production per Plant Sample (g), and Production per Plot (kg). The result of statistical analysis showed that PGR Hantu with 4 cc / l water (Z2) showed the highest yield on all observed age with yield of plant height 24,04 cm and leaf number 14,85 piece at age 4 MST, and yield production per plant sample 152.75 g andproduction per plot of 3.79 kg. The highest dose of NPK Tawon fertilizer that is 56,25 (N3) showed the highest yield with yield of plant height 23,23 cm and leaf number 14,61 piece at age 4 MST, and yield production per plant sample 148,89 g and production per plot 3.68 kg. The interaction of PGR Hantu and NPK Tawon fertilizer showed no significant effect on growth of mustard pakchoy plant.